Turkey : Report on the Observance of Standards and Codes-Data Module; Response by the Authorities, and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report, 2002)
This Report on the Observance of Standards and Codes provides a review of Turkey's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS) complemented by an in-depth assessment of the quality of the national accounts, consumer and producer price indices, government finance, monetary, and balance-of-payments statistics. The findings reveal that Turkey subscribes to the SDDS. Turkish statistical agencies in the main have a legal and institutional framework that supports statistical quality. Agencies demonstrate an awareness of quality as the cornerstone of statistical work.